SEEDLING EMERGENCE AND GENETIC PARAMETERS OF OPEN-POLLINATED CANDEIA PROGENIES GROWN IN TREE NURSERY - Avelar, Maria Lopes Martins; Silva Júnior, Vitor Passos da; Rosado, Lucas Rodrigues; Gonçalves, Flávia Maria Avelar; Pavan, Adriano José; Melo, Lucas Amaral de (Floresta, 2021)
MacLeish is economically appreciated due to its wood and to the extraction of its essential oil, whose active principle is alpha-bisabolol. Despite its economic importance, studies about the genetic breeding of this species remain scarce. The aim of the current study is to determine E. erythropappus seedling emergence rate, genetic parameters, as well as to identify potential open-pollinated progenies of this species and their respective matrices. The experiment was set up in tree nursery, based on a completely randomized design, with 22 progenies in four replicates comprising 14 plants per plot. Seedling emergence rate was evaluated 30 days after seeding, whereas plant height (H) and stem diameter (SD) were measured at 100 days. Statistical analyses were carried out based on the REML/BLUP method. Three progenies have shown seedling emergence rate lower than 50%; this value is considered limiting to seedling production process. Genetic variation was observed among progenies, as well as high and positive genetic correlation between H and SD. Thus, it was possible identifying superior progenies and matrices, as well as the ones presenting low performance in the evaluated traits.